NEW PAPER FORMAT & SUBMISSION GUIDELINES —————————————————————->>>>> PDF - *, * (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2019)
Please download this document and use the NEW FORMAT introduced for the current Edition to be published in 2020. Submit your paper in the MS-Doc file format only.